The Relevance of John Dewey's Thinking to Contextual Learning in the Era of Independent Learning - Sahjad M. Aksan; Adiyana Adam; Kamarun M. Sebe; Sutria Ningsih Hairudin (Tinta Emas Institute, 2025)
The rapid transformation of education in the 21st century demands approaches that move beyond traditional, teacher-centered instruction toward models that are more student-centered, experiential, and contextually relevant. In Indonesia, this shift is embodied in the Independent Curriculum (Kurikulum Merdeka), which emphasizes curriculum flexibility, local contextualization, and the active role of teachers in adapting instruction to students’ needs and environments. Within this context, John Dewey’s philosophy of progressive education, which underscores learning through experience, critical reflection, and social engagement, offers an important theoretical foundation for understanding and strengthening contemporary pedagogical practices. This study aims to examine the relevance of Dewey's educational philosophy to the implementation of contextual learning within the Independent Curriculum by employing a qualitative descriptive approach based on library research. Drawing on analyses of Dewey’s seminal works, educational policy documents, scholarly publications, and documented examples of curriculum application in schools such as SMAN 10 Kota Ternate, SDN Tomagoba Tidore, and SLB Sofifi in North Maluku, the study finds that Dewey’s principles—learning by doing, real-life experience, and student-centered engagement—are strongly reflected in current practices of contextual learning. The documented evidence highlights positive outcomes, including increased student motivation, active participation, and improved effectiveness of the learning process. These findings affirm the enduring relevance of Dewey’s educational philosophy in addressing the demands of 21st-century education and underscore the necessity of sustained policy support and continuous professional development for teachers to ensure the successful implementation of the Independent Curriculum.